Identification of long-chain alkane-degrading (LadA) monooxygenases in Aspergillus flavus via in silico analysis - Perera, Madushika; Wijesundera, Sulochana; Wijayarathna, C. Dilrukshi; Seneviratne, Gamini; Jayasena, Sharmila (Frontiers in Microbiology, 2022)
Efficient degradation of alkanes in crude oil by the isolated Aspergillus flavus MM1 alluded to the presence of highly active alkane-degrading enzymes in this fungus. A long-chain alkane-degrading, LadA-like, enzyme family in A. flavus, was identified and possible substrate binding modes were analysed using a computational approach. By analysing publicly available protein databases, we identified six uncharacterized proteins in A. flavus NRRL 3357, of which five were identified as class LadAα and one as class LadAβ, eukaryotic homologs of bacterial long-chain alkane monooxygenase, LadA. Computational models of A. flavus LadAα homologs (Af1-Af5) showed overall structural similarity to the bacterial LadA and the unique sequence and structural elements that bind the cofactor, FMN. A receptor-cofactor-substrate docking protocol was established and validated to demonstrate the substrate binding in the A. flavus LadAα homologs. The modelled Af1, Af3, Af4, and Af5, captured long-chain n-alkanes inside the active-pocket, above the bound FMN. Isoalloxazine ring of reduced FMN formed a π-alkyl interaction with the terminal carbon atom of captured alkanes, C16 to C30, in Af3-Af5 and C16 to C24 in Af1. Our results confirmed the ability of identified A. flavus LadAα monooxygenases to bind long-chain alkanes inside the active pocket. Hence A. flavus LadAα monooxygenases potentially initiate the degradation of long-chain alkanes by oxidizing bound long-chain alkanes into their corresponding alcohol.